Characterization of triboelectrically charged particles deposited on dielectric surfaces - Nesterov-Müller, Alexander; Löffler, F.; Cheng, Yun-Chien; Torralba, Gloria Collados; König, Kristina; Hausmann, Michael; Lindenstruth, Volker; Stadler, Volker; Bischoff, F. Ralf; Breitling, F. (Journal of physics. D, Applied physics, 2010)
A device for the measurement of q/m-values and charge degradation of triboelectrically charged particles deposited on a surface was developed. The setup is based on the integration of currents, which are induced in a Faraday cage by insertion of a solid support covered with charged particles. The conductivity of different particle supports was taken into account. The ‘blow-off’ method, in which the particles are first deposited, and then blown off using an air stream, can be used for characterization of triboelectric properties of particles relative to different surfaces.